Efficacy of post‐induction therapy for high‐risk neuroblastoma patients with end‐induction residual disease. Issue 15 (6th June 2022) - Desai, Ami V.; Applebaum, Mark A.; Karrison, Theodore G.; Oppong, Akosua; Yuan, Cindy; Berg, Katherine R.; MacQuarrie, Kyle; Sokol, Elizabeth; Hall, Anurekha G.; Pinto, Navin; Wolfe, Ian; Mody, Rajen; et al.
Abstract : BACKGROUND: High‐risk neuroblastoma patients with end‐induction residual disease commonly receive post‐induction therapy in an effort to increase survival by improving the response before autologous stem cell transplantation (ASCT). The authors conducted a multicenter, retrospective study to investigate the efficacy of this approach. METHODS: Patients diagnosed between 2008 and 2018 without progressive disease with a partial response or worse at end‐induction were stratified according to the post‐induction treatment: 1) no additional therapy before ASCT (cohort 1), 2) post‐induction "bridge" therapy before ASCT (cohort 2), and 3) post‐induction therapy without ASCT (cohort 3). χ 2 tests were used to compare patient characteristics. Three‐year event‐free survival (EFS) and overall survival (OS) were estimated by the Kaplan‐Meier method and survival curves were compared by log‐rank test. RESULTS: The study cohort consisted of 201 patients: cohort 1 (n = 123), cohort 2 (n = 51), and cohort 3 (n = 27). Although the end‐induction response was better for cohort 1 than cohorts 2 and 3, the outcomes for cohorts 1 and 2 were not significantly different ( P = .77 for EFS and P = .85 for OS). Inferior outcomes were observed for cohort 3 ( P < .001 for EFS and P = .06 for OS). Among patients with end‐induction stable metastatic disease, 3‐year EFS was significantly improved for cohort 2 versus cohort 1 ( P = .04). Cohort 3 patients with a complete response at metastatic sites after post‐induction therapy had significantly better 3‐year EFS than those with residual metastatic disease ( P = .01). CONCLUSIONS: Prospective studies to confirm the benefits of bridge treatment and the prognostic significance of metastatic response observed in this study are warranted.